Comparative analysis and student response relationships regarding the inquiry learning model on students' attitudes and character - Astalini Astalini; Darmaji Darmaji; Dwi Agus Kurniawan; Miftahul Zannah Azzahra (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research was conducted with the aim of knowing the differences and the relationship between student responses to the inquiry learning model, student attitudes towards physics lessons and student character towards physics lessons in class XI IPA 1 and XI IPA 4 at SMAN 11 Jambi City. This research uses quantitative research with associative and comparative research types, by filling out a questionnaire. The sampling technique used in this research is purposive sampling. Based on the results of the hypothesis testing carried out, it can be concluded that there are differences and relationships between students' responses to the inquiry learning model on students' attitudes and character in physics subjects.